Risk premia on Swiss government bonds and sectoral stock indexes during international crises - Thomas Nitschka (Aussenwirtschaft, 2016)
This paper assesses the sensitivity of excess returns on Swiss government bond and sectoral stock indexes to risk factors during international crisis and non-crisis periods over the sample period from January 1995 to December 2014. The empirical results show that assets that were closely linked to the Swiss economy, such as government bonds or stocks from "non-tradable" sectors, exhibited safe haven characteristics during the Eurozone sovereign debt crisis and in the noncrisis periods. This finding does not pertain to assets closely linked to international economic developments, such as stocks from tradable goods sectors.
Keywords: G01; G10; G12; 330; Asset pricing; Bond returns; International crisis; Stock returns